2022
DOI: 10.3390/ph15050528
|View full text |Cite
|
Sign up to set email alerts
|

Moringa oleifera Leaf Extract Promotes Healing of Infected Wounds in Diabetic Rats: Evidence of Antimicrobial, Antioxidant and Proliferative Properties

Abstract: Moringa oleifera is known to possess wound healing activity. The present study evaluated the healing properties of methanolic extract of M. oleifera leaves in excision wounds infected with methicillin-resistant Staphylococcus aureus (MRSA) or P. aeruginosa in diabetic rats. An in vitro study was also carried out to determine the gene expression of VEGF and TGF-β1. Preliminary phytochemical and GC-MS analyses were carried out to determine different chemical constituents present in the extract. M. oleifera was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 44 publications
(43 reference statements)
1
12
0
Order By: Relevance
“…The results of the current study on infected wounds in normal rats support our findings on the effect of M. oleifera extract on the infected wounds in diabetic rats [ 19 ]. In our earlier study, we analyzed the chemical constituents of M. oleifera by GC-MS to show the presence of volatile constituents.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The results of the current study on infected wounds in normal rats support our findings on the effect of M. oleifera extract on the infected wounds in diabetic rats [ 19 ]. In our earlier study, we analyzed the chemical constituents of M. oleifera by GC-MS to show the presence of volatile constituents.…”
Section: Discussionsupporting
confidence: 90%
“…The cytotoxicity of the extract and its effect on the expression of VEGF and TGF-β1 genes were evaluated using HaCaT cells. The study was a continuation of our report on the effect of M. oleifera extract on infected wounds in diabetic rats [ 19 ].…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Also, [ 19 ] mentioned the ecologically friendly manufacture of silver nanoparticles from fresh leaves of the Moringa oleifera plant and evaluated against Escherichia coli , Klebsiella pneumonia , Staphylococcus aureus, and Bacillus subtilis . Moringa contains a long list of medical use including antibacterial [ 20 ], antifungal [ 21 ], antiparasitic [ 22 ], antiviral [ 23 ], wound healing, antimicrobial, antioxidant, and proliferative properties [ 24 ]. In the present study, we evaluated the effectiveness of the synthesis of silver nanoparticles from aqueous extract of Moringa oleifera leaves extract against the clinical strain of bacteria (positive and negative Gram) and human pathogenic fungi ( Candida species)and evaluated the cytotoxicity effect of silver nanoparticles on human skin cancer.…”
Section: Introductionmentioning
confidence: 99%
“…These phytoconstituents act as bioactive organic compounds such as alkaloids, flavonoids, glycosides, phenols, saponins, tannins, terpenoids, reducing sugars, and triglycerides [ 4 ]. Most of the previous studies on Moringa oleifera have shown that the presence of phenolic compounds contributes to different antimicrobial and antioxidant properties [ 5 , 6 , 7 , 8 , 9 ]. Furthermore, the extraction of these phytochemicals through different solvents shows a very effective inhibition activity against microbes [ 10 ].…”
Section: Introductionmentioning
confidence: 99%